Discordant prostate specific antigen test results despite WHO assay standardization. Issue 3 (August 2018) - Boegemann, Martin; Arsov, Christian; Hadaschik, Boris; Herkommer, Kathleen; Imkamp, Florian; Nofer, Jerzy-Roch; Gerß, Joachim; Albers, Peter; Semjonow, Axel
Introduction: Total PSA (tPSA) and free PSA (fPSA) are the most commonly used biomarkers for early detection of prostate cancer. Despite standardization efforts, many available PSA assays may still produce discordant results. In the present study, we compared four PSA assays calibrated to the WHO standards 96/670 and 96/668 for tPSA and fPSA, respectively. Methods: Within the scope of the Prostate Cancer Early Detection Study Based on a ''Baseline'' PSA Value in Young Men (PROBASE), we tested tPSA and fPSA in serum samples from 50 patients in the four different PROBASE sites using four WHO-calibrated assays from Roche (Elecsys, Cobas), Beckman-Coulter (Access-II) and Siemens (ADVIA Centaur). The comparison was performed using the Passing–Bablok regression method. Results: Compared to Access, the median tPSA levels for Centaur, Elecsys, and Cobas were +3%, +11%–20%, and +17%–23%, respectively, while for median fPSA levels the differences for Centaur, Elecsys, and Cobas were +49%, +29%–31%, and +22%, respectively. Discussion: Despite all investigated assays being WHO-calibrated, the Elecsys and Cobas tPSA assays produced considerably higher results than the Access and Centaur assays. Differences in fPSA-recovery between all investigated assays were even more pronounced. When applying the tPSA cutoff of 3.1 μg/L recommended for WHO-calibrated assays, the use of higher calibrated assays may lead to unnecessary prostate biopsies. Conversely, if the historical threshold of 4 μg/L is applied when using WHO-calibrated assays, it could lead to falsely omitted prostate biopsies.